Nonseparable Uhf Algebras Ii: Classification - Farah, Ilijas; Katsura, Takeshi (MATHEMATICA SCANDINAVICA, 2015)
For every uncountable cardinal $κ$ there are $2^κ$ nonisomorphic simple AF algebras of density character $κ$ and $2^κ$ nonisomorphic hyperfinite ${\rm II}_1$ factors of density character $κ$. These estimates are maximal possible. All C*-algebras that we construct have the same Elliott invariant and Cuntz semigroup as the CAR algebra.